ON THE ISSUE OF THE NEED TO USE MOBILE POINTS OF WEIGHT AND SIZE CONTROL IN THE REPUBLIC OF UZBEKISTAN - Khalmukhamedov A. S.; Omarov J. A.; Anvarjonov A. A. (Galaxy International Interdisciplinary Research Journal, 2022)
Non-compliance by road users with established norms and rules in the field of transportation of oversized and heavy cargo creates a real threat to the life and health of citizens, as evidenced by statistical data on road accidents and deaths in road traffic accidents and leads to negative economic consequences, causing damage both state property, which includes the highway as a property complex of engineering and technical structures, and vehicles of various forms of ownership, incl. personal property of citizens. A significant influence on the wear and destruction of the road pavement of the carriageway and roadsides is exerted by the factor of exceeding the permissible axle loads of freight vehicles, the indicators of which have a pronounced upward trend on most public roads. Currently, work is underway in the Republic of Uzbekistan to create a system of weight and dimensional control of vehicles that would allow for the inspection of cargo vehicles and ensure the collection of funds to compensate for damage caused to roads. In the period 2020-2022 deployment and operation of 52 points of weight and size control are envisaged. The analysis shows that this quantity of PVHC planned for installation is 52 units. not enough to create a system.This will lead to an increase in the load on the roads of international, state and local significance that remain without weight and size control, which means a decrease in road safety, an increase in the number of places of concentration of accidents, a lack of protection of roads of these categories from the movement of trucks with overload, and a decrease in their overhaul periods. In this situation, based on the international experience of developed countries, the solution to the problem is proposed in the use of mobile points of weight and size control - PPVGK. The article considers and generalizes the experience of foreign countries in the field of weight and size control of cargo ATSPPVGK. It is proposed to equip the regional territorial departments of the Committee for Automobile Roads under the Ministry of Transport of the Republic of Uzbekistan with PPVCs.